Study on the content of the game and efficiency of actions of center in volleyball player - Cojocaru, A. M.; Cojocaru, M. (Science, Movement & Health, 2013)
The present paper entitled "Study on the game content and the efficiency of the center player in volleyball game" consist in analyzing model, due to essential changes occurred in the current competitive game content: increased speed of the game, increasing the strength of the attack, execution and service the lock and specific features of the takeover of attack changes due mainly to new changes in the regulation. Hypothesis. That the game of volleyball is carried out by certain fundamental characteristics due to application and effectiveness of the game the players that make the team, printed features training model, determine the positions of the game, the players involved and the center position becomes an objective necessity which may lead to increased whole team game parameters. There have been a few tasks off our research literature including information on the state of knowledge on the chosen topic, gathering information and data on game content in zone 3, in terms of weight and overall efficiency of game actions and for the two structures, analysis of results, their interpretation and separation of the most important conclusions of the theoretical and practical, which can be helpful in charge of training specialists. Method. Mathematical processing of data from records is preferable to meet international standards developed by the FIVB, so we can relate to them (summarized by M. Serban, 1998 and 1999). Their scaling on 5 levels, as follow: 0 = wrong (-); 1 = keeping the ball in play to limit error (-0); 2 = continuation phase with limited tactical actions (0); 3 = optimal condition for continuation phase (+0); 4 = point (+). The last level (4 = +) is found only decisive action: service, attack after reception, attack after digger and block. For the other actions: reception, setter after reception, digger. and setter after digger have only four levels, the latter being seen as a great (3 = + 0 ) as there are actions completed and linking players play the same team. Conclusions. Research conclusions have been systemized on issues that were derived from the general hypothesis of the study.